1978
DOI: 10.1007/bf01685785
|View full text |Cite
|
Sign up to set email alerts
|

The influence of selenium on the level of mercury and metallothionein in rat kidneys in prolonged exposure to different mercury compounds

Abstract: Mercuric chloride, phenylmercuric chloride, ethylmercuric chloride /0,23 mg Hg/kg/ and methylmercurycyan guanidine /0,46 mg Hg/kg/ were orally administered to rats every second day for 14 weeks. The same doses of the above mentioned mercury compounds were administered alternately with sodium selenite /0,18 mg Se/kg/ to parallel groups of rats at the same time. The level of total and inorganic mercury and of metallothionein was determined. All mercury compounds increased the level of metallothionein in rat kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Apart from the soluble fraction in the kidneys, Environmental Health Perspectives (37,40,(51)(52)(53).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the soluble fraction in the kidneys, Environmental Health Perspectives (37,40,(51)(52)(53).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is accompanied by about a fivefold diminution of mercury concentration in the kidneys and inhibition of metallothionein biosynthesis (26,27,(64)(65)(66). Simultaneously a distinct, about fourfold increase of the level of this metal is observed, especially in the mitochondrial and nuclear fractions (26) and concentration of mercury in the blood increases considerably (25,27,67).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the concentration ofmetallothioneinlike proteins, highly correlated with the level of inorganic mercury, was observed after prolonged exposure of rats to ethylmercuric chloride and methylmercuric Tanoguanidine (48). It was also demonstrated that Me 03Hg (49,51), methoxyethyl 203Hg (49) and Et203Hg (52) are bound by low molecular weight proteins of the soluble fraction of rat kidneys.…”
Section: Introductionmentioning
confidence: 78%
“…The presence of selenium inhibits the stimulation of biosynthesis of metallothioneinlike proteins by inorganic mercury (47,48,(59)(60)(61)(62)(63). Our previous studies (51,52) have dealt with the metabolism of methyl-and ethylmercuric chloride in rats in the presence and absence of selenium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation